The paradoxical mindset of systems engineers : uncommon minds, skills, and careers - Pyster, Arthur B.; Hutchison, Nicole, 1982-; Henry, Devanandham, 1974- (John Wiley & Sons, 2018)
The Paradoxical Mindset of Systems Engineers offers an in-depth look at the proficiencies and personal qualities effective systems engineers require and the positions they should seek for successful careers. The book also gives employers practical strategies and tools to evaluate their systems engineers and advance them to higher performance. The authors explore why systems engineers are uncommon and how they can assess, improve, and cleverly leverage their uncommon strengths. These insights for being an ever more effective systems engineer apply equally well to classic engineers and project managers who secondarily do some systems engineering.
Keywords: Systems engineering -- Vocational guidance.; Engineers -- Psychological aspects.; elektronické knihy; electronic books